2017
DOI: 10.1016/j.atherosclerosis.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Identifying low density lipoprotein cholesterol associated variants in the Annexin A2 ( ANXA2 ) gene

Abstract: Background and aimsAnnexin-A2 (AnxA2) is an endogenous inhibitor of proprotein convertase subtilisin/kexin type-9 (PCSK9). The repeat-one (R1) domain of AnxA2 binds to PCSK9, blocking its ability to promote degradation of low-density lipoprotein cholesterol-receptors (LDL-R) and thereby regulate low-density lipoprotein cholesterol (LDL-C) levels. Here we identify variants in ANXA2 influencing LDL-C levels and we determine the molecular mechanisms of their effects.ResultsThe ANXA2 single nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The data obtained have revealed an association of the minor allele of the ANXA2 gene with a higher level of LDL-C, which corresponds to the previous data [21]. Carriage of a rare allele has been associated with a decrease in the effectiveness of the statin.…”
supporting
confidence: 87%
“…The data obtained have revealed an association of the minor allele of the ANXA2 gene with a higher level of LDL-C, which corresponds to the previous data [21]. Carriage of a rare allele has been associated with a decrease in the effectiveness of the statin.…”
supporting
confidence: 87%
“…Over recent years, a substantial number of additional studies identified correlations between disease progression and expression patterns of individual annexins; as is the case in many cancer and other acute and chronic diseases [ 1 , 2 , 3 , 21 , 22 , 23 , 90 , 116 , 226 , 242 , 342 , 343 , 368 , 369 ]. However, aided by deep sequencing data, various SNPs were identified, suggesting a potential involvement of AnxA1 in Alzheimer’s disease [ 436 ], and revealed roles for AnxA2 in sickle cell disease [ 119 , 120 ], but also cardiovascular risk due to elevated LDL cholesterol [ 114 , 149 ]. Similarly, the identification of SNPs in the Anxa3 gene locus may imply roles in gastric cancer [ 437 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, adenoviral AnxA2 overexpression elevated hepatic LDLR levels in vivo [ 114 ]. The association of LDL-cholesterol levels with Anxa2 gene variants [ 149 ] support modulation of AnxA2 levels as a potential cholesterol-lowering strategy. Applicable for obesity and the metabolic syndrome, AnxA2 depletion attenuated obesity-induced insulin resistance through suppression of NFκB signaling [ 150 ].…”
Section: Anxa2mentioning
confidence: 99%
“…AnxA2 interacts with insulin and insulin-like growth factor receptors [ 17 ], and is phosphorylated and sumoylated upon insulin stimulation [ 18 , 19 ], possibly relevant for cell adhesion [ 17 ], but also translocation of the glucose transporter type 4 (GLUT4) in adipocytes [ 20 ]. Moreover, AnxA2 regulates mouse extrahepatic low density lipoprotein receptor (LDLR) levels in vivo [ 21 , 22 ], which correlates with elevated LDL cholesterol levels in humans carrying AnxA2 gene variants [ 23 ]. Loss of AnxA7 was linked to abnormal insulin secretion [ 24 ]; however, these findings were challenged by others [ 25 ].…”
Section: Introductionmentioning
confidence: 99%